PENERAPAN MODEL PEMBELAJARAN STAD BERBANTUAN MEDIA AUGMENTED REALITY UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI SISWA SD - Alviena Tazky Amalia; Lilik Bintarik; Aldi Surya Kinasih; Amida Suaidah; Devi Restu Putpitasari; Hinggar Relung Puspita; Sinta Kiswoyo Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the collaboration skills of third-grade students at SDN Bareng 3 Malang in the IPAS subject through the application of the Student Teams Achievement Divisions (STAD) cooperative learning model aided by Augmented Reality (AR) media. The background of this study is the students’ low collaboration skills, characterized by a tendency to work individually, a lack of positive interaction, and the dominance of certain students in group discussions. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted over three cycles. Research data were collected through observation, interviews, and validation questionnaires, then analyzed using descriptive qualitative and quantitative methods. The results showed that integrating the STAD model with AR media successfully improved students’ collaboration skills gradually, with the average percentage of students’ collaboration skills reaching 72.15% in Cycle I (good category), 84.12% in Cycle II (very good category), and 91.63% in Cycle III (very good category). This improvement is supported by the characteristics of the STAD model, which emphasizes individual and group responsibility, as well as AR technology, which facilitates structured role-sharing and more immersive interactions in learning activities. These findings conclude that the AR-assisted STAD learning model is effective in creating an active and collaborative learning environment and can serve as a reference for educators in developing 21st-century skills among elementary school students.